Social engagement with parents in 11-month-old siblings at high and low genetic risk for autism spectrum disorder. (November 2015) - Campbell, Susan B; Leezenbaum, Nina B; Mahoney, Amanda S; Day, Taylor N; Schmidt, Emily N
Infant siblings of children with an autism spectrum disorder are at heightened genetic risk to develop autism spectrum disorder. We observed high risk ( n  = 35) and low risk ( n  = 27) infants at 11 months during free play with a parent. Children were assessed for autism spectrum disorder in toddlerhood. High-risk infants with a later diagnosis ( n  = 10) were less socially engaged with their parents than were low-risk infants. Parent behavior during play did not vary by group. Within the high-risk group, ratings of social reciprocity at 11 months predicted Autism Diagnostic Observation Schedule severity scores at follow-up, suggesting that systematic observations of parent–infant play may be a useful addition to early assessments of emerging autism spectrum disorder.